Dampak Alih Fungsi Perkebunan Karet ke Kelapa Sawit Bagi Kesejahteraan Petani Desa Kebun Agung Kecamatan Pangkalan Banteng Kabupaten Kotawaringin Barat - Musthofa, Khabib (AL-QARDH, 2020)
ABSTRACTThis research is a phenomenon of the function of rubber to oil palm plantations carried out by farmers in the village of Kebun Agung, Pangkalan Banteng District, Kotawaringin Barat Regency. The aims of this study how the background causes of rubber farmers to switch to being an oil palm farmer in Kebun Agung Village. Second, how is the impact on the welfare of rubber farmers after being converted into oil palm farmers in Kebun Agung Village. The purpose of this study is to find out the background that causes rubber farmers to convert their plantations into oil palms and the impact on the welfare of farmers. This research is a qualitative research with a descriptive approach. The subject was focused on 9 farmers by sampling using purposive sampling techniques.The results of this study indicate that the background of the cause of rubber farmers to switch to being an oil palm farmer in Kebun Agung Village, Pangkalan Banteng District, Kotawaringin Barat Regency is work as a rubber farmer that is done every day while the price is cheap so that farmers' income is not enough to meet economic needs. Whereas palm oil works only once every two weeks are more expensive than rubber and are sufficient to meet daily needs. The impact of the welfare of the rubber farmer's family after being converted into an oil palm farmer in Kebun Agung Village, Pangkalan Banteng District, Kotawaringin Barat Regency is a positive impact for farmers, their income increases, their work is lighter, their assets are increased, and their families feel more prosperous than before.ABSTRAKPenelitian ini adalah fenomena alih fungsi perkebunan karet ke kelapa sawit yang dilakukan petani desa Kebun Agung Kecamatan Pangkalan Banteng Kabupaten Kotawaringin Barat. Fokus masalah pada penelitian ini adalah bagaimana latar belakang